2018
DOI: 10.1111/ahe.12386
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical study of Ki‐67 protein, androgen receptor, and estrogen receptor beta in testicular tissues of male pigs immunocastrated with different times of GnRH vaccination

Abstract: This study aimed to investigate the immunoexpression of Ki-67 protein, androgen receptor (AR), and estrogen receptor beta (ERβ) in testicular tissues of male pigs immunocastrated using GnRH vaccine (Improvac™, Zoetis Co., Ltd., Thailand) with different times. Totally, 30 male pigs were classified by castration protocol into three groups: T1 (n = 10) consisted of pigs immunocastrated at 14 and 18 weeks of age, T2 (n = 10) included pigs immunocastrated at 9 and 19 weeks of age, and C (n = 10) contained intact pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
(28 reference statements)
0
2
0
Order By: Relevance
“…In this study, immunohistochemical reaction of ERα was detected both in the seminiferous tubules and interstitial areas. Likewise, our earlier study reported that ERβ is also localized both in Leydig cells and seminiferous tubules of the male fattening pigs (Srisuwatanasagul et al, 2018). This was because estrogen is an indispensable hormone for regulating Sertoli cell development and spermatogenesis within the seminiferous tubules (At-Taras et al, 2006), as well as the development of Leydig cells in the interstitial areas (Abney, 1999).…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…In this study, immunohistochemical reaction of ERα was detected both in the seminiferous tubules and interstitial areas. Likewise, our earlier study reported that ERβ is also localized both in Leydig cells and seminiferous tubules of the male fattening pigs (Srisuwatanasagul et al, 2018). This was because estrogen is an indispensable hormone for regulating Sertoli cell development and spermatogenesis within the seminiferous tubules (At-Taras et al, 2006), as well as the development of Leydig cells in the interstitial areas (Abney, 1999).…”
Section: Discussionmentioning
confidence: 64%
“…Apart from histology, certain studies investigating the testicular gross morphology have reported that the testicles of immunocastrated pigs are smaller and lighter than those of the intact pigs (Zamaratskaia et al, 2008;Brunius et al, 2011;Einarsson et al, 2011;Kubale et al, 2013). Moreover, our previous study demonstrated that testicular length, measured between both apexes, of the intact pigs is more than that of the immunocastrated pigs (Srisuwatanasagul et al, 2018). As for the timing of immunocastration, our earlier study confirmed that the first GnRH vaccine administration either at 9 or 15 weeks of age contributes to comparable testicular length and histomorphometric parameters, including the height of spermatogenic epithelia, the diameter of seminiferous tubules, and the number of seminiferous tubules (Srisuwatanasagul et al, 2021).…”
Section: Discussionmentioning
confidence: 88%